An acute episode of rhabdomyolysis associated with everolimus and cabergoline intake in a postpartum kidney recipient - B. I. Yaremin; E. V. Parabina; U. V. Maslikova; V. E. Aleksandrova (Трансплантология (Москва))
Kidney transplantation is one of the most promising ways to ensure the onset and successful maintenance of pregnancy in patients with end-stage chronic renal disease. A multicomponent drug therapy in such patients creates risks for fetal development, primarily due to the teratogenicity of mTOR receptor inhibitors and mycophenolate. Moreover, the inhibitors of the proliferative signal may have potential drug interactions, which can result in additional complications.Rhabdomyolysis is one of them. The paper describes the clinical case of an acute episode of reversible rhabdomyolysis in a patient on everolimus therapy.